DIGITAL STORYTELLING SEBAGAI MEDIA PEMBELAJARAN YANG KREATIF DAN INOVATIF DI ERA NEW NORMAL - Paulina Fortinasari; Candradewi Wahyu Anggraeni; Susanti Malasari (Politeknik Negeri Sriwijaya, 2022)
The rapid development of technology and limited learning condition during the current pandemic require teachers as educators to be able to integrate technology into classroom activities appropriately and effectively. Digital storytelling is a form of modern learning media that can be used as an alternative to deliver material as well as insert character values that must be acquired by the elementary school students during this pandemic. This article discusses the implementation of training on making digital storytelling as a creative and innovative learning medium for elementary school teachers. It also reveals the perceptions of the teachers regarding the use of digital storytelling in the class. There are four stages of training, namely observation, socialization, mentoring, and evaluation. Through these stages, this training received positive responses from the participants and successfully provided direct benefits to the elementary school teachers. The participants had participated in the training enthusiastically and actively did the practices of making digital storytelling. All the digital storytelling made were very interesting, high-quality and full of character values that the students need to develop during the condition of learning from home.